Leprosy neuropathy and demyelinating impairment: How should we interpret this neurophysiological pattern? - Diogo Fernandes dos Santos; Iago Resende Carvalho; Isabella Sabião Borges; Pedro Henrique Sirotheau Corrêa Alves1; Fernanda de Oliveira Cirino; Douglas Eulálio Antunes; Raquel Campos Pereira; Marcus Vinicius Magno Gonçalves; Isabela Maria Bernardes Goulart (PLoS ONE, 2026)
Introduction/Aims Leprosy neuropathy (LN) may cause demyelination that worsens during the leprosy reactions (LR). Type-1 LR (T1LR) occurs in patients with cell-mediated immune response against M. leprae, and Type-2 LR (T2LR) occurs in multibacillary cases. The patterns of nerve impairment need to be clarified, as both demyelination and axonal degeneration are commonly observed. This study aimed to describe how to interpret the demyelinating impairment in LN. Methods Retrospective observational analysis of leprosy patients in a National Reference Center in Brazil between 2014–2023. Results 494 participants were included in this study. 3952 nerves were evaluated, with an average of 5.1 (±5.4) nerves affected per patient. 23.5% (116/494) of patients showed a demyelinating pattern defined by standard criteria, and 20.7% (24/116) presented exclusively demyelinating abnormalities without evidence of secondary axonal loss. 81% (94/116) presented conduction block, and 95.7% (111/116) temporal dispersion, with both conditions concomitant in 76.7% (89/116) of patients. 83.6% (97/116) demonstrated prolonged distal motor latency, and 99.1% (115/116) reduction in conduction velocity. 46.1% had T1LR and 17.9% T2LR. The comparison between patients with and without LR showed higher bacillary load, conduction block, and temporal dispersion in LR patients. 93.1% (108/116) of patients fulfilled neurophysiological criteria for chronic inflammatory demyelinating polyneuropathy (CIDP). Among them, 46.3% presented clinical criteria for atypical CIDP. Discussion Leprosy is a spectral disease in which neural damage can manifest in different phenotypes. Demyelinating impairment is frequent and varies according to the clinical form and presence of LR. Although demyelinating impairment is common in the studied population, it does not reflect active disease. LN can also be misdiagnosed as other peripheral neuropathies, especially CIDP, in non-endemic areas.